319Congenital cytomegalovirus education, translation and prevention. (2nd September 2021) - Waight, Emma; Swinburn, Katherine; Shand, Antonia; Hui, Lisa; Daly, Kate; Rawlinson, William; Jones, Cheryl; Badawi, Nadia; Smithers-Sheedy, Hayley
Abstract: Focus of Presentation: Congenital cytomegalovirus (CMV) is a known cause of sensorineural hearing loss, cerebral palsy and other disabilities. International consensus guidelines (2017) and the Australasian Society of Infectious Diseases (2014) recommend all pregnant women be provided with information on CMV and strategies to reduce their risk of infection. Here we describe the multifaceted strategies implemented to date to promote uptake of these guidelines. Findings: At policy level, we influenced national clinical practice standards through input into new CMV prevention recommendations by the Royal Australian and New Zealand College of Obstetricians and Gynaecologists and Department of Health, which sparked state public health campaigns. At the intervention level, we presented hospital in-services, podcasts and webinars and developed an e-learning course for midwives. In collaboration with the Department of Health >11, 000 pamphlets were disseminated to NSW GPs. At the community level, we developed patient information and media resources. During a recent month-long campaign, our cCMV video had >62, 000 views, CMV content on social media had >1.4M total impressions, >77, 000 total engagements and >200, 000 viewed CMV awareness pieces via television/radio/print. Conclusions/Implications: Implementation of congenital CMV practice guidelines provide an important opportunity to prevent neurodevelopmental disability. Collaborations between families, clinicians, researchers, professional bodies and health departments are essential to drive translation. Key messages: A multifaceted approach in implementing congenital CMV practice guidelines gives the opportunity to reach numerous stakeholders including policymakers, health professionals and expectant mothers.